Genetic Diversity of Musa balbisiana Colla in Indonesia Based on AFLP Marker - RITA MEGIA; YUYU SURYASARI POERBA; FAJARUDIN AHMAD (HAYATI Journal of Biosciences, 2014)
Musa balbisiana Colla, known as Pisang Klutuk/Pisang Batu, is important for banana breeding program due to its B genome and often considered  to be resistant to pest, disease and drought.  Banana is a big and tall herb up to 7-9 m in height.The study was conducted to assess genetic diversity of 21 accessions of M. balbisiana cultivars/varieties from Indonesia based on Amplified Fragment Length Polymorphism (AFLP) markers in order to provide basic information to support banana breeding program. Analyses of similarity index of Nei and Li and clustering based on UPGMA was conducted using NTSYS program. Principal Component Analysis (PCA) was conducted by MINITAB 14. Twenty two primer pairs of AFLP markers produced 485 AFLP bands varying from 51-3206 bp in size and 46.18% of the AFLP bands were polymorphic. Genetic diversity among the 21 accessions of M. balbisiana was 13.8%. The genetic diversity of wild M. balbisiana was 12.9%, higher than the genetic diversity of cultivated M. balbisiana which was 11.5%. Cluster analysis based on UPGMA suggested that wild M. balbisiana and cultivated M. balbisiana could not be separated into different clusters. Both cluster analysis and PCA produced the same three groups of the accessions. The PCA analyses showed that 17 AFLP bands were responsible for the grouping.